1993
DOI: 10.1111/j.1365-2036.1993.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Short report: high‐dose omeprazole and amoxycillin in the treatment of Helicobacter pylori‐associated duodenal ulcer

Abstract: Thirteen consecutive patients with active duodenal ulcer disease were assigned to a treatment schedule with high-dose omeprazole and amoxycillin. Duodenal ulcer was diagnosed endoscopically in all patients, at which time antral biopsies were taken for culture and histology. All were positive for Helicobacter pylori and histological gastritis. Treatment was for 2 weeks : 80 mg omeprazole daily plus 500 mg amoxycillin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Amoxicillin and PPI dual therapy eventually fell into disfavor because it did not reliably produce high cure rates and it was replaced by triple therapy consisting of a PPI, amoxicillin, and clarithromycin or metronidazole [16]. However, a number of studies suggested that good success rates for H. pylori eradication could be obtained with dual therapy if the dose of the PPI were increased [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Improved results were also obtained by increasing the PPI dose with triple therapy, and it appears that this improvement was most likely related to the increase in treatment success based on improvement in the dual PPIamoxicillin component of the triple therapy [14,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Amoxicillin and PPI dual therapy eventually fell into disfavor because it did not reliably produce high cure rates and it was replaced by triple therapy consisting of a PPI, amoxicillin, and clarithromycin or metronidazole [16]. However, a number of studies suggested that good success rates for H. pylori eradication could be obtained with dual therapy if the dose of the PPI were increased [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Improved results were also obtained by increasing the PPI dose with triple therapy, and it appears that this improvement was most likely related to the increase in treatment success based on improvement in the dual PPIamoxicillin component of the triple therapy [14,33,34].…”
Section: Introductionmentioning
confidence: 99%